Cysteamine in Maturation Medium Enhances Nuclear Maturation and Fertilization Rate of Sheep Oocytes In Vitro - Feni Dwi Kartika Gulo; Ni Wayan Kurniani Karja; Mohamad Agus Setiadi (Bogor Agricultural University, Indonesia, 2020)
Low nuclear maturation and fertilization rate is one obstacle in the in vitro embryo production which decrease embryo yield. This problem is presumable related with high production of reactive oxygen species (ROS) during maturation process. Glutathione (GSH) as an antioxidant is well known to overcome effect of ROS production. GSH synthesis in the cytosol part of the oocyte cytoplasm is influenced by cysteine availability. It is therefore, this research was conducted to evaluate the ability of cysteamine to provide cysteine availability as GSH precursor on the nuclear maturation and fertilization rate of sheep oocytes. Results of this experiment revealed additional cysteamine at 150 µm and 200 µm could significantly improve nuclear maturation rate. On the other side, although additional of cysteamine at 50 µm could not improve nuclear maturation rate, however 50 µm cysteamine in the maturation medium could significantly improve the fertilization rate. Based on those experiment results, it seems that the additional cysteamine might be improve not only GSH availability but also the oocyte quality which characterized the ability of pronuclear formation. This finding strongly suggested that additional cysteamine in the maturation medium could improve nuclear maturation and fertilization rate of sheep oocytes.